Kontaminasi Mikroplastik pada Ikan Kiper (Scatophagus argus) dari Laguna Segara Anakan, Cilacap - Hidayati, Nuning Vita; Hotijah, Siti; Hudawi, Mohammad Nuh; Andriyono, Sapto; Sanjayasari, Dyahruri; Hastuti, Dewi Wisudyanti Budi; Hendrayana, Hendrayana (Rekayasa, 2023)
Microplastics are pollutants of emerging concern today. The presence of microplastics in fish from several marine environments has been reported worldwide. This study examined the presence of microplastics in the gastrointestinal tract (GIT) of the Kiper Fish (Scatophagus argus) from the Segara Anakan Lagoon, Cilacap, Central Java. Microplastics were found with an average abundance of 22.22 ± 6.8 items/ind. Fragment (45%) was the main type of microplastic found in the analyzed Kiper fish, followed by fiber (27%), film (21%), and pellets (7%). Eight types of colors were found in the analyzed fish, with black (43%) and transparent (33%) being the predominant plastic colors. There were 12 types of microplastic polymers found, namely Polystyrene (PS), Nylon, Polymethyl methacrylate (PMMA), Cellulose acetate (CA), Polycarbonate (PC), Polyvinyl chloride (PVC), Polypropylene (PP), Polyurethane (PU), Latex, Acrylonitrile butadiene stryrene (ABS), High-density polyethylene (HDPE), Polyethylene telephthalate (PETE). The results of this study indicate that more serious attention must be paid to the handling of plastic waste, given the accumulation of high amounts of microplastics in fish, which can be harmful to human health.